Оптимізація 3d ассетів для підвищення продуктивності ігрових систем - Науменко, Д. В. (ХНУРЕ, 2024)
In the world of 3D gaming, optimizing 3D models is crucial to creating an immersive gaming experience. This involves balancing visual quality with game performance to ensure detailed environments and an enjoyable gameplay experience. Poor optimization can lead to slower gameplay and poor performance. The optimization process involves converting high-poly models into low-poly versions without losing important details. One method is retopology, where the location of vertices, edges, and faces of a high-poly model are mapped to a low poly model to preserve defining features while reducing the number of polygons. Baking is another technique that mimics the complex details of a high poly model into a low-poly model by using a normal map for surface details.
Keywords: продуктивність ігрових систем